Development of Android-Based Educational Media Using AppyPie on Pascal’s Law to Enhance Problem-Solving Skills Among 11th-Grade Students - vilana, Mirna; Yanti, Fitri April; Setiawan, Iwan (Jurnal Pendidikan Fisika, 2026)
This study was motivated by the limited availability of learning materials designed to improve students’ problem-solving skills. The study aims to develop an Android-based learning tool using AppyPie on Pascal programming concepts to enhance the problem-solving skills of 11th-grade students. The research method employed a research and development approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research instruments used include an expert validation questionnaire and a student response questionnaire. Data analysis utilized both quantitative and qualitative data. The average product feasibility validation score was 85.51%, indicating that the developed product is highly suitable for use. The improvement in students’ problem-solving skills falls into the moderate category with an N-Gain value of 0.60. These results indicate that the use of Android-based learning media with the assistance of AppyPie is capable of improving students’ problem-solving skills. Student response results received an average rating of 93%, with student responses to the development of the learning media categorized as “very good,” meaning that the developed media possesses appeal and elicits a positive response from students. This research supports student-centered learning and enhances problem-solving skills.